Result Analysis of Hash Value Generation Using Security Algorithm for Device Forensics - Kapse, Arvind S; Thakare, Vilas M; Kapse, Avinash S (International Journal of Computer Sciences and Engineering, 2025)
Digital forensics tools are often used to calculate the hash value of the digital test unit. The MD5 and SHA hash function is used in digital forensics tools to calculate and verify that a dataset has not been altered, due to the application of multiple collection and analysis tools and procedures of evidence. In addition, because of the impact on the personal life of the subject of the survey, the verification of the proper functioning of the tools and procedures is crucial. This article discusses the importance of hashing value in digital forensics for digital evidence. The search uses six different possible cases as an experiment to generate and verify the hash value of the test drive by using a forensic tool to demonstrate the importance of the hash value in digital forensics. In addition, unreliable results can be obtained due to incorrect use of the Tools application